Conceptual approaches to studying migration used to contemporary Chinese migration to Kazakhstan - Болдуруковa Н.Б., Н Б.; Жaнaтaевa У.К. У К. (Journal of Oriental Studies, 2017)
The article discusses the theoretical aspects of the studying of Chinese migration. Characteristics of migration from China to Kazakhstan is suitable to theory of international migration. These patterns was researched in migration concepts, and will not be an exaggeration to say that most of them are applicable to case of these two countries. The author tries to explain the current trends in Chinese migration to Kazakhstan through the prism of conceptual approaches to the studying of migration processes.